Determinación de aflatoxinas M1 (AFM1) en leche bovina producida en cuatro predios de la sabana de Bogotá. (2021)
Considering that milk it's a food highly marketed as well as of high consumption, it's crucial to know its quality and safety, since concerning the permitted level of aflatoxins these have been showing to cause adverse effects in humans and animals, especially it is noted a carcinogenic affect the liver and the exposition can cause the parenchyma degeneration followed of carcinoma and cirrhosis. For this reason, the presence of Aflatoxin M1 was determined in some dairy farms in the southern area of Bogota to analyze the levels of aflatoxin M1 using the high-performance chromatography test, which allows us to obtain an accurate and precise result.